Characterization and impact of graphene oxide on the curing and mechanical properties of epoxy resins - Jimenez, Gina Maritzell Colmenares; Oliveira, Adhimar Flávio; Carneiro, Tessa Martins de Carvalho; Wanderley Neto, Estacio Tavares; Gonzalez, Maria Elena Leyva (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2025)
Graphene oxide (GO) has been widely studied as a nanofiller for epoxy resins due to its excellent mechanical, thermal, and interfacial properties. In this study, GO was synthesized via electrochemical exfoliation and characterized using FTIR, XRD, TGA, and SEM. GO was incorporated into an epoxy matrix (Litestone 3200 resin with 2131H hardener) at different weight percentages (0.10%, 0.13%, 0.20%, and 0.50%), and the curing behavior was analyzed through differential scanning calorimetry (DSC). The cure kinetics were evaluated using the Kissinger and Ozawa methods. The results indicated that the activation energy increased at 0.13% GO but decreased at higher concentrations. TGA analysis showed that the addition of GO improved thermal stability, particularly at 0.10% GO. FTIR confirmed the presence of oxygenated functional groups in GO, XRD indicated partial exfoliation and structural disorder, and SEM revealed sheet-like morphology. These results were consistent and complementary, supporting the successful incorporation of GO into the epoxy network. The addition of GO slightly improved the mechanical modulus without significantly altering the glass transition temperature (Tg).